Structural equation modeling - Bowen, Natasha K.; Guo, Shenyang (New York ; Oxford : Oxford University Press, 2012)
Richly illustrated with figures, equations, matrices, and tables, this pocket guide empowers social workers with a set of defensible analysis strategies that allows for competent confident use of SEM.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Data processing; Social service -- Research; Structural equation modeling